Water-responsive shape memory effect in tough hydrogel - Sun, Yi Jie (2019)
Hydrogels has gained its popularity among researchers in recent years due to its unique properties. Many studies were conducted since it was introduced, and it had been used widely in a large variety of applications. For example, hydrogel is utilized for biomedical application due to its biocompatibility. In biomedical application, there was a little research about how hydrogel could provide support when there is rupture in blood vessels. Common hydrogels such as water babies do not have such ability because they become fragile after swelling process in water. Gaps between hydrogels and blood vessels should be avoided. Hence fragile hydrogels with low strength cannot be selected for this experiment. Tough hydrogel was introduced because of its hardness and elasticity at fully wet condition. It was studied in this project in terms of its swelling ratio, moisture content and response time. A tough hydrogel sample with drilled hole in the center was used to observe the buckling effect by multiple approaches.